The Protection Problems and Reparations of Ahi Celebi Mosque in Istanbul - Ozakin, Rabia; Erdem, Ayten (TRANS TECH PUBLICATIONS LTD, 2010)
The Ahi Celebi Mosque, which is among Istanbul's oldest mosques, is located on the shores of the Golden Horn in the Eminonu. This mosque, which was very probably built by Ahi Celebi towards the end of the 15(th) century, was restored during the 16(th) century by Architect Sinan. It is a stone building with a rectangular plan, single dome, with a rear congregational area/son cemaat yeti in front of its main space, and a cut stone minaret at its right corner. Damaged by fires and earthquakes during its long history, this building, set on reclaimed land, was restored and strengthened at various times through the years. In the 1980s, the building was unfavourably affected by the construction of the new Galata Bridge; it began to sink and slide towards the sea, with the result that it had to be supported with steel girdles as a temporary measure and was abandoned. In 2000, the General Directorate of Foundations had concrete pillars added underground to stabilise the base, and the sea water around the foundations was pumped out. During the last restoration carried out in 2005-2006, the main dome and walls were strengthened, the minaret was rebuilt, and the interior plaster and decorations were redone. In this study we shall make a general re-evaluation of the restoration work undertaken on the 500 year old Ahi Celebi Mosque. We shall determine to what degree the structural interventions and, in particular, the contemporary interventions have been able to maintain the original materials, shapes, workmanship and period additions, and whether or not these are distinguishable, reversible and suitable to the aesthetics of the whole.
Keywords: Turkey; mosque; consolidation; structural damage; historical evidence; Construction & Building Technology; Engineering; Materials Science